2004
DOI: 10.1002/anie.200353461
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Hydration of Nitriles to Amides in Water, Catalyzed by Ruthenium Hydroxide Supported on Alumina

Abstract: A broad range of amides is accessible in excellent yield (>99 %) by hydration of the corresponding nitriles in water in the presence of the supported ruthenium catalyst Ru(OH)x/Al2O3 (see scheme). For example, the industrially important conversion of acrylonitrile into acrylamide was achieved in quantitative yield and better than 99 % selectivity. The catalyst can be reused without loss of catalytic activity and selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
102
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 222 publications
(108 citation statements)
references
References 27 publications
6
102
0
Order By: Relevance
“…[12] The Rh(OH) x /Al 2 O 3 -catalyzed hydration of nitriles likely proceeds by a mechanism similar to that of a previously reported Ru(OH) x /Al 2 O 3 -catalyzed hydration (steps 3 and 4 in Scheme 1). [13] The reaction rate is independent of the concentration of D 2 O, which indicates that O À H bond dissociation is not the ratelimiting step. The reaction of 6 a (PhCH=NOH) and adeuteriobenzaldoxime (PhCD=NOH) gave a kinetic isotope effect (k H /k D ) of 3.1 AE 0.4 under the conditions described in Table 1, which suggests that C À H bond cleavage (step 2 in scheme 1) is the rate-limiting step.…”
mentioning
confidence: 99%
“…[12] The Rh(OH) x /Al 2 O 3 -catalyzed hydration of nitriles likely proceeds by a mechanism similar to that of a previously reported Ru(OH) x /Al 2 O 3 -catalyzed hydration (steps 3 and 4 in Scheme 1). [13] The reaction rate is independent of the concentration of D 2 O, which indicates that O À H bond dissociation is not the ratelimiting step. The reaction of 6 a (PhCH=NOH) and adeuteriobenzaldoxime (PhCD=NOH) gave a kinetic isotope effect (k H /k D ) of 3.1 AE 0.4 under the conditions described in Table 1, which suggests that C À H bond cleavage (step 2 in scheme 1) is the rate-limiting step.…”
mentioning
confidence: 99%
“…Inspired by this pioneering work, we prepared various types of supported metal hydroxide catalysts for nitrile hydration. Fortunately, we found that nitrile hydration showed high catalytic activity and selectivity 14) . The potential of the Ru(OH)x /Al2O3-catalyst system for the synthesis of various types of structurally diverse nitriles is summarized in Fig.…”
Section: )mentioning
confidence: 95%
“…The present review article summarizes our achievements with heterogeneously catalyzed green functional group transformations using supported metal hydroxide catalysts as follows: (i) oxidative dehydrogenation of alcohols and amines by Ru(OH)x/Al2O3 10) 13) , (ii) hydration of nitriles by Ru(OH)x/Al2O3 14) , (iii) ammoxidation of primary alcohols by Ru(OH)x/Al2O3 15), 16) , (iv) formal α-oxygenation of primary amines by Ru(OH)x / Al2O3 17) , (v) oxidative homocoupling of terminal alkynes by Cu(OH)x /OMS-2 18) , and (vi) 1,3-dipolar cycloaddition of azides to terminal alkynes by Cu(OH)x / TiO2 19) .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, metal complexes have been used to access amides through the dehydrogenative reaction between amines and alcohols or aldehydes. 9,10 Furthermore, the hydration of nitriles 11 and the rearrangement of aldoximes 12,13 can also provide alternative synthetic routes to amides. Very recently, Sekar and coworkers developed an efficient process for the direct synthesis of amides from methylarenes and amines using an iron catalyst.…”
Section: Introductionmentioning
confidence: 99%